2022
DOI: 10.1111/jmp.12618
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of cryopreserved organs from the gastrointestinal system of squirrel monkeys (Saimiri sciureus, Linnaeus, 1758) for improvement of management

Abstract: Background Nonhuman primates (NHPs) are fundamental for countless types of research and their phylogenetic similarities with humans make them valuable biomodels. Saimiri (squirrel monkeys) is the New World simian genus that is most widely used in research; however, little is known about the morphology of the gastrointestinal tract (GIT) of these animals. Methods The morphological and topographical aspects of GIT organs from 14 previously frozen carcasses of captive squirrel monkeys (Saimiri sciureus) were desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It is thought that these correlations may be very useful in revealing sexual dimorphism features in mice and in various clinical application areas. Andrade et al (2023) reported in their study on squirrel monkeys (Saimiri sciureus Linnaeus, 1758) that the length measurements of the tongue and esophagus were 3.0 cm and 12.7 cm, respectively, in males. Additionally, in the same study, they calculated the weight of the tongue as 2.2 g in males and 1.9 g in females.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is thought that these correlations may be very useful in revealing sexual dimorphism features in mice and in various clinical application areas. Andrade et al (2023) reported in their study on squirrel monkeys (Saimiri sciureus Linnaeus, 1758) that the length measurements of the tongue and esophagus were 3.0 cm and 12.7 cm, respectively, in males. Additionally, in the same study, they calculated the weight of the tongue as 2.2 g in males and 1.9 g in females.…”
Section: Discussionmentioning
confidence: 98%
“…In general, numerous studies have been conducted to determine the anatomical, morphological, and morphometric characteristics of the other digestive system organs, including the tongue and esophagus concerning sexual dimorphism in other animals as well as laboratory animals (Yıldız et al, 2001;Walters et al, 2014;Igado et al, 2015;Gırgırı et al, 2015;Sahd et al, 2017;Bełżecki et al, 2018;Jaji et al, 2019;Ayırtır Başdinç, 2023;Andrade et al, 2023). When examining the morphometric measurement values in our study, it was seen that all measurement values obtained from both Swiss Albino and Balb-c mice were higher in males compared to females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation